Preparation method and application of steel slag emulsified asphalt mixture

CN122940408APending Publication Date: 2026-10-20GAOYUAN HIGHWAY MAINTENANCE TECH HENAN PROV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611048564.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0010]本发明解决的技术问题是提供了一种钢渣乳化沥青混合料的制备方法和应用,以解决现有技术中未陈化钢渣活性组分引起的体积安定性风险较大、乳化沥青混合料在常温条件下成型压实困难以及树脂类增强组分界面作用效果有限等问题,该方法利用未陈化钢渣的反应活性作为触发源,并在碾压成型过程中利用钢渣中游离氧化钙与酸性组分的原位酸碱反应放热,依次触发相变密封组分熔融、低沸点动力源气化以及环氧树脂保压固化,使未陈化钢渣无需长时间陈化即可用于乳化沥青混合料的制备

Benefits of technology

[0023]1、制备过程步骤S1中先将环氧树脂与相变密封组分加热熔融混合,再冷却至过冷液态后加入低沸点动力源使得相变密封组分以过冷态均匀分散于树脂基质中而不立即结晶,低沸点动力源也能以液态稳定存在于体系中。在步骤S3的降温处理阶段,过冷态的相变密封组分获得足够的过冷度驱动力,在疏水颗粒间隙中发生结晶形成锁定层,将低沸点动力源和环氧树脂封存于壳体内部,保证了微胶囊在常温储存和拌和阶段的稳定性,使其仅在碾压触发时才释放内部组分。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a method for preparing and applying steel slag emulsified asphalt mixture, belonging to the field of road engineering materials technology. First, epoxy resin, phase change sealing components, and a low-boiling-point power source are prepared into an oil phase, and an acidic component and a water-based curing agent are prepared into an aqueous phase. These are then emulsified and assembled into shells to obtain microcapsules. Next, the microcapsules are mixed with steel slag coarse aggregate, fine aggregate and / or mineral powder, and emulsified asphalt, spread, and compacted. During compaction, the microcapsules rupture and release heat, promoting sealing, pressurization, and resin curing, thereby improving the volume stability, compaction, and interfacial adhesion of the mixture, making it suitable for road maintenance engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] This invention belongs to the field of road engineering materials technology, specifically relating to a method for preparing and applying steel slag emulsified asphalt mixture. Background Technology

[0004] Steel slag, a major industrial solid waste, is effectively recycled through its application in road engineering. Meanwhile, emulsified asphalt mixture technology is widely used in road maintenance due to its advantages such as ambient temperature construction and energy conservation and emission reduction. With the development of green transportation technologies, combining steel slag with emulsified asphalt mixture technology holds promise for achieving a complementary advantage in both solid waste disposal and ambient temperature construction.

[0005] Applying unaged steel slag directly to emulsified asphalt mixtures is one of the most direct ways to improve resource utilization. However, steel slag typically contains active components such as free calcium oxide, especially insufficiently aged steel slag, which is prone to hydration reactions and volume expansion when exposed to water, thus posing a risk to the volume stability of the mixture. Existing technologies usually reduce the activity of steel slag through natural aging, but this type of treatment has drawbacks such as long processing time, large footprint, and inconvenience in application.

[0006] Meanwhile, emulsified asphalt mixtures exhibit high internal frictional resistance at room temperature, making compaction difficult. The rough surface and numerous sharp edges of steel slag coarse aggregate further increase the compaction difficulty during mixture formation, easily leading to larger voids and consequently affecting its water stability and durability. Furthermore, although some studies have attempted to introduce epoxy resins to improve aggregate interfacial bonding performance, the relatively high viscosity of these resins at room temperature makes it difficult for them to effectively penetrate the deep pores of the steel slag, thus limiting their improvement on interfacial bonding and durability.

[0007] The prior art patent document CN202311603487.8 discloses a modified steel slag aggregate asphalt mixture and its preparation method. The raw materials of the modified steel slag aggregate asphalt mixture include steel slag aggregate, RO fly ash, modified fibers, amino resin modified asphalt, and stearate modified limestone powder. RO fly ash and modified fibers are uniformly dispersed on the surface of the steel slag aggregate to form modified steel slag aggregate. Amino resin modified asphalt coats the modified steel slag aggregate to form the steel slag asphalt mixture. Stearate modified limestone powder fills the pores of the steel slag asphalt mixture. This modified steel slag aggregate asphalt mixture is designed with a multi-stage anti-expansion structure, fundamentally solving the problem of steel slag asphalt mixture easily expanding and causing pavement damage. It effectively enhances the stability of steel slag and significantly improves the road performance and service life of the steel slag asphalt mixture. Patent document CN202210807156.5 discloses a waterborne epoxy resin emulsified asphalt cold-mix steel slag mixture and its preparation method. The waterborne epoxy resin emulsified asphalt cold-mix steel slag mixture comprises the following components by weight: 0.8-1.0 parts waterborne epoxy resin system, 5.6-7.0 parts emulsified asphalt, 93.5-94 parts steel slag aggregate, 4.5-5.5 parts steel slag powder, 1.0-1.5 parts cement, and 2.0-2.5 parts water. This waterborne epoxy resin emulsified asphalt cold-mix steel slag mixture has good road performance, low pollution, low emissions and low energy consumption. It can effectively solve the problems of poor low-temperature performance, poor early water stability and strength of cold-mix asphalt mixtures, and poor engineering economy and high energy consumption of hot-mix steel slag mixtures. It realizes the high-value and large-scale utilization of steel slag solid waste and extends the service life of road construction. Neither of the aforementioned patent documents contains any record of using the reactivity of unaged steel slag as a trigger source, and utilizing the in-situ acid-base reaction between free calcium oxide in the steel slag and acidic components during the rolling process to release heat, thereby sequentially triggering the melting of phase change sealing components, the gasification of low-boiling-point power sources, and the pressure-holding curing of epoxy resin, so that unaged steel slag can be used for the preparation of emulsified asphalt mixtures without long-term aging.

[0008] Therefore, providing a steel slag emulsified asphalt mixture and its preparation method that can simultaneously improve the stability of steel slag, the compaction performance of the mixture, and the bonding effect of aggregates under normal temperature mixing and mechanical rolling conditions remains a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0010] The technical problem solved by this invention is to provide a method for preparing and applying steel slag emulsified asphalt mixtures, in order to solve the problems in the prior art such as the large risk of volume stability caused by the active components of unaged steel slag, the difficulty of molding and compacting emulsified asphalt mixtures under normal temperature conditions, and the limited interfacial effect of resin-based reinforcing components. This method uses the reactivity of unaged steel slag as a trigger source, and in the rolling molding process, it utilizes the exothermic in-situ acid-base reaction between free calcium oxide in the steel slag and acidic components to sequentially trigger the melting of phase change sealing components, the gasification of low-boiling-point power source, and the pressure-holding curing of epoxy resin, so that unaged steel slag can be used to prepare emulsified asphalt mixtures without long-term aging.

[0011] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: a method for preparing steel slag emulsified asphalt mixture, the specific preparation steps of which are as follows:

[0012] Step S1: Mix epoxy resin with phase change sealing component and heat until phase change sealing component melts. After cooling, add low boiling point power source to obtain oil phase. The phase change sealing component includes fatty acid phase change material and tackifying resin. The low boiling point power source is a low boiling point organic component with a normal pressure boiling point of 20~45℃.

[0013] Step S2: Mix the acidic component with the aqueous curing agent to obtain an aqueous phase, wherein the acidic component is an aqueous solution of organic acid and the aqueous curing agent is a polyamine curing agent;

[0014] Step S3: The aqueous phase obtained in step S2 is added to the oil phase obtained in step S1, and emulsified to form a water-in-oil primary emulsion. The primary emulsion is then dispersed in an outer aqueous phase containing hydrophobic particles for shell assembly. After cooling, the phase change sealing component crystallizes in the gaps between the hydrophobic particles to form a locking layer and obtain microcapsules. The hydrophobic particles are hydrophobically modified nano-silica.

[0015] Step S4: The microcapsules obtained in step S3 are mixed with unaged steel slag coarse aggregate, fine aggregate and / or mineral powder, emulsified asphalt and water at room temperature. After spreading, the mixture is mechanically compacted. The compaction causes the microcapsules to rupture and release acidic components. The acidic components react with the free calcium oxide in the steel slag to release heat, which promotes the melting of the phase change sealing components, the gasification of the low boiling point power source and the curing of the epoxy resin, and finally forms a steel slag emulsified asphalt mixture.

[0016] Further specifying, the epoxy resin in step S1 is a bisphenol A type epoxy resin; the phase change sealing component includes stearic acid and hydrogenated rosin glycerol ester; and the low-boiling-point power source is isopentane.

[0017] Further specifying, the acidic component in step S2 is an aqueous solution of acetic acid; and the aqueous curing agent is tetraethylenepentamine.

[0018] Further specified, the heating temperature in step S1 is 80~90℃, and the target temperature after cooling is 25~35℃; the cooling temperature in step S3 is 10~15℃.

[0019] Further specified, the shear speed for forming the water-in-oil primary emulsion in step S3 is 2000~5000 rpm; the particle size of the unaged steel slag coarse aggregate in step S4 is ≤15 mm.

[0020] Further specifying, based on the total mass of the mineral aggregate, the amount of the unaged steel slag coarse aggregate is 65wt%~75wt%, and the amount of the fine aggregate and / or mineral powder is 25wt%~35wt%; per 100 parts by weight of mineral aggregate, the amount of the microcapsules is 1.0~2.0 parts, and the amount of the emulsified asphalt is 3.0~5.0 parts.

[0021] The steel slag emulsified asphalt mixture prepared by this invention is used as a road maintenance engineering material, and its application scenario is cold-laid thin-layer overlay.

[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0023] 1. In step S1 of the preparation process, epoxy resin and phase change sealing component are first heated and melted together, then cooled to a supercooled liquid state. A low-boiling-point kinetic energy source is then added to ensure the phase change sealing component is uniformly dispersed in the resin matrix in a supercooled state without immediate crystallization. The low-boiling-point kinetic energy source also remains stably present in the system in a liquid state. In the cooling stage of step S3, the supercooled phase change sealing component receives sufficient supercooling driving force, causing crystallization to occur in the gaps between hydrophobic particles, forming a locking layer. This seals the low-boiling-point kinetic energy source and epoxy resin inside the shell, ensuring the stability of the microcapsules during room temperature storage and mixing, and ensuring that the internal components are released only upon crushing triggering.

[0024] 2. In step S4 of the preparation process, after the microcapsules are crushed, the acidic components react with the free calcium oxide in the steel slag to form an acid-base neutralization reaction that releases heat. This reaction consumes the free calcium oxide while providing local heat, reducing the content of active components in the steel slag that cause volume expansion, and reducing the risk of the mixture expanding when exposed to water in the later stage. As a result, the unaged steel slag can be used directly for the preparation of the mixture without long-term natural aging, which greatly shortens the solid waste disposal cycle.

[0025] 3. The localized heat generated by the acid-base reaction melts the phase change sealing component inside the microcapsule. When the phase change sealing component contains both fatty acid-based phase change materials and tackifying resins, the resulting mixed fluid has a high viscosity. This allows it to form a seal at the microcapsule opening and in the rough gaps of the surrounding aggregate surface, reducing the lateral escape of gas after the low-boiling-point power source vaporizes. This facilitates the transmission of pressure generated by vaporization along the micropores of the aggregate.

[0026] 4. The low-boiling-point power source vaporizes under the heat of reaction, generating internal pressure. Under the condition that the phase change sealing components form a seal, the pressure generated by vaporization acts on the surrounding aggregate particles, producing microscopic disturbances. This reduces the frictional resistance between aggregate particles in the emulsified asphalt multiphase system, promotes particle rearrangement and void closure, and improves the compaction effect of the mixture under normal temperature conditions. At the same time, this internal pressure drives liquid epoxy resin into the micropores on the surface of the steel slag along the pressure direction, overcoming the deficiency that epoxy resin, due to its high viscosity, cannot easily penetrate deep pores by capillary action alone.

[0027] 5. Epoxy resin comes into contact with a water-based curing agent and undergoes cross-linking and curing under maintained internal pressure. The resin cured under pressure exerts extrusion pressure on the pore walls, offsetting the tensile stress generated at the interface due to volume shrinkage during resin curing. This enhances the adhesion between the resin and the micropore walls of the aggregate, improving the interfacial and water stability of the mixture.

[0028] 6. This invention integrates acidic components, water-based curing agents, epoxy resin, phase change sealing components, and low-boiling-point power sources into the same microcapsule system, enabling the exothermic acid-base reaction, sealing layer formation, vaporization pressurization, and resin curing processes to occur synergistically during room-temperature mixing and compaction molding. This eliminates the need for separate treatment of steel slag stability, room-temperature compaction, and resin interface enhancement, simplifying the process path.

[0029] 7. During the mixing stage, the microcapsules exhibit a waxy lubricating state due to the supercooled co-crystallization locking structure of the phase change sealing components, which is conducive to the uniform dispersion and paving of the mixture. After compaction, they quickly transform into a highly adhesive resin-reinforced state. The entire process can be carried out at room temperature without the need for additional heating equipment or long-term steel slag pretreatment. This makes them particularly suitable for high-standard road maintenance projects, with significant energy saving, emission reduction and economic benefits. Detailed Implementation

[0031] This invention integrates acidic components, epoxy resin, phase change sealing components, and a low-boiling-point power source into microcapsules. By utilizing the exothermic reaction between steel slag and acidic components during the compaction molding process, the sealing, pressurization, and curing processes are triggered sequentially, thereby achieving the room-temperature preparation and molding of unaged steel slag emulsified asphalt mixture.

[0032] To better illustrate the above technical solutions, detailed descriptions will be provided below with reference to specific embodiments. However, this should not be construed as limiting the scope of the present invention to the following embodiments; all technologies implemented based on the above content of the present invention fall within the scope of the present invention.

[0033] The performance tests of the mixture were conducted in accordance with the current Chinese test procedures for asphalt and asphalt mixtures for highway engineering. The test items were void ratio, freeze-thaw splitting strength ratio (TSR), and water swelling rate.

[0034] Example 1

[0035] Step S1: Weigh 300 parts by weight of bisphenol A type epoxy resin (E-51, epoxy equivalent 186-192 g / eq) and 40 parts by weight of butyl glycidyl ether (diluent), stir and mix evenly, add 45 parts by weight of stearic acid and 10 parts by weight of hydrogenated rosin glycerol ester, heat to 85°C, stir at 300 rpm until the mixture is completely melted and transparent, rapidly cool to 30°C to make the mixture in a supercooled liquid state, add 40 parts by weight of isopentane, stir at 200 rpm for 5 minutes to mix evenly to obtain the oil phase.

[0036] Step S2: Mix 150 parts by weight of acetic acid aqueous solution (concentration 30wt%) with 100 parts by weight of tetraethylenepentamine to obtain an aqueous phase.

[0037] Step S3: At 28℃, the aqueous phase obtained in step S2 is slowly added to the oil phase obtained in step S1 at a rate of 10 mL / min, and high-speed shear emulsification is performed at 3500 rpm for 10 minutes to form a water-in-oil primary emulsion; 50 parts by weight of hydrophobically modified nano-silica (R974, particle size 12 nm) is ultrasonically dispersed (300W, 10 minutes) in 250 parts by weight of deionized water, and the external aqueous phase is obtained by maintaining the temperature at 35℃; the water-in-oil primary emulsion is added to the external aqueous phase and dispersed at 2000 rpm for 15 minutes to assemble the shell; then the system temperature is rapidly reduced to 12℃ at a rate not lower than 10℃ / min and maintained for 20 minutes to allow stearic acid and hydrogenated rosin glycerol ester to crystallize in the gaps of nano-silica to form a locking layer, and the microcapsules are obtained by filtration and separation. The obtained microcapsules are spherical with an average particle size of about 200 μm.

[0038] Step S4: Based on the total mass of the aggregate, weigh 70 wt% of unaged steel slag coarse aggregate (particle size ≤15 mm, free calcium oxide content approximately 3.5 wt%), 28.5 wt% of limestone fine aggregate and mineral powder, 1.5 parts by weight of the microcapsules prepared in Step S3 per 100 parts by weight of aggregate, 4.0 parts by weight of cationic slow-cracking emulsified asphalt (solid content 60%) per 100 parts by weight of aggregate, and an appropriate amount of water. Dry mix the above materials at 25°C for 30 seconds, add the emulsified asphalt and water, wet mix for 60 seconds until the color is uniform, fill into a standard Marshall mold (φ101.6 mm), compact on both sides 75 times, demold, and cure at room temperature to obtain steel slag emulsified asphalt mixture specimens. During the compaction process, the sharp edges of the steel slag coarse aggregate cause the microcapsules to rupture. The released acetic acid aqueous solution reacts with the free calcium oxide in the steel slag, generating heat and promoting the melting of stearic acid and hydrogenated rosin glycerol ester, the vaporization of isopentane, and the cross-linking and curing of epoxy resin and tetraethylenepentamine.

[0039] Comparative Example 1 (excluding low-boiling-point power sources)

[0040] Step S1: Weigh 300 parts by weight of bisphenol A type epoxy resin (E-51) and 40 parts by weight of butyl glycidyl ether and stir to mix evenly. Add 45 parts by weight of stearic acid and 10 parts by weight of hydrogenated rosin glycerol ester, heat to 85°C, and stir at 300 rpm until the mixture is completely melted and transparent. Rapidly cool to 30°C to make the mixture in a supercooled liquid state to obtain the oil phase.

[0041] Step S2: Mix 150 parts by weight of acetic acid aqueous solution (concentration 30wt%) with 100 parts by weight of tetraethylenepentamine to obtain an aqueous phase.

[0042] Step S3: At 28℃, the aqueous phase obtained in step S2 is slowly added to the oil phase obtained in step S1 at a rate of 10 mL / min, and high-speed shear emulsification is performed at 3500 rpm for 10 minutes to form a water-in-oil primary emulsion; 50 parts by weight of hydrophobic modified nano silica (R974) is ultrasonically dispersed in 250 parts by weight of deionized water, and the external aqueous phase is obtained by maintaining the temperature at 35℃; the water-in-oil primary emulsion is added to the external aqueous phase, and the shell is assembled by dispersing at 2000 rpm for 15 minutes. Then the system temperature is suddenly dropped to 12℃ and maintained for 20 minutes. The microcapsules are obtained by filtration and separation.

[0043] Step S4: Based on the total mass of the aggregate, weigh 70 wt% of unaged steel slag coarse aggregate (particle size ≤15 mm, free calcium oxide content approximately 3.5 wt%), 28.5 wt% of limestone fine aggregate and mineral powder, 1.5 parts by weight of the microcapsules prepared in Step S3 per 100 parts by weight of aggregate, 4.0 parts by weight of cationic slow-cracking emulsified asphalt per 100 parts by weight of aggregate, and an appropriate amount of water. Dry mix at 25°C for 30 seconds, add emulsified asphalt and water, wet mix for 60 seconds until the color is uniform, fill into a standard Marshall mold (φ101.6 mm), compact on both sides 75 times, demold, and cure at room temperature to obtain the mixture specimen.

[0044] Comparative Example 2 (excluding phase change sealing components)

[0045] Step S1: Weigh 300 parts by weight of bisphenol A type epoxy resin (E-51) and 40 parts by weight of butyl glycidyl ether and stir to mix evenly. Add 40 parts by weight of isopentane at 30°C and stir at low speed of 200 rpm for 5 minutes to mix evenly to obtain the oil phase.

[0046] Step S2: Mix 150 parts by weight of acetic acid aqueous solution (concentration 30wt%) with 100 parts by weight of tetraethylenepentamine to obtain an aqueous phase.

[0047] Step S3: At 28℃, the aqueous phase obtained in step S2 is slowly added to the oil phase obtained in step S1 at a rate of 10 mL / min, and high-speed shear emulsification is performed at 3500 rpm for 10 minutes to form a water-in-oil primary emulsion; 50 parts by weight of hydrophobic modified nano silica (R974) is ultrasonically dispersed in 250 parts by weight of deionized water, and the external aqueous phase is obtained at 35℃; the water-in-oil primary emulsion is added to the external aqueous phase, and the shell is assembled at 2000 rpm for 15 minutes. Then the system temperature is suddenly dropped to 12℃ and held for 20 minutes. The microcapsules are obtained by filtration and separation.

[0048] Step S4: Based on the total mass of the aggregate, weigh 70 wt% of unaged steel slag coarse aggregate (particle size ≤15 mm, free calcium oxide content approximately 3.5 wt%), 28.5 wt% of limestone fine aggregate and mineral powder, 1.5 parts by weight of the microcapsules prepared in Step S3 per 100 parts by weight of aggregate, 4.0 parts by weight of cationic slow-cracking emulsified asphalt per 100 parts by weight of aggregate, and an appropriate amount of water. Dry mix at 25°C for 30 seconds, add emulsified asphalt and water, wet mix for 60 seconds until the color is uniform, fill into a standard Marshall mold (φ101.6 mm), compact on both sides 75 times, demold, and cure at room temperature to obtain the mixture specimen.

[0049] Comparative Example 3 (without acidic components, using an equal amount of deionized water instead of acetic acid aqueous solution)

[0050] Step S1: Weigh 300 parts by weight of bisphenol A type epoxy resin (E-51) and 40 parts by weight of butyl glycidyl ether and stir to mix evenly. Add 45 parts by weight of stearic acid and 10 parts by weight of hydrogenated rosin glycerol ester, heat to 85°C, and stir at 300 rpm until the mixture is completely melted and transparent. Rapidly cool to 30°C to make the mixture a supercooled liquid. Add 40 parts by weight of isopentane and stir at 200 rpm for 5 minutes to mix evenly to obtain the oil phase.

[0051] Step S2: Mix 150 parts by weight of deionized water with 100 parts by weight of tetraethylenepentamine to obtain an aqueous phase.

[0052] Step S3: At 28℃, the aqueous phase obtained in step S2 is slowly added to the oil phase obtained in step S1 at a rate of 10 mL / min, and high-speed shear emulsification is performed at 3500 rpm for 10 minutes to form a water-in-oil primary emulsion; 50 parts by weight of hydrophobic modified nano silica (R974) is ultrasonically dispersed in 250 parts by weight of deionized water, and the external aqueous phase is obtained at 35℃; the water-in-oil primary emulsion is added to the external aqueous phase, and the shell is assembled at 2000 rpm for 15 minutes. Then the system temperature is suddenly dropped to 12℃ and held for 20 minutes. The microcapsules are obtained by filtration and separation.

[0053] Step S4: Based on the total mass of the aggregate, weigh 70 wt% of unaged steel slag coarse aggregate (particle size ≤15 mm, free calcium oxide content approximately 3.5 wt%), 28.5 wt% of limestone fine aggregate and mineral powder, 1.5 parts by weight of the microcapsules prepared in Step S3 per 100 parts by weight of aggregate, 4.0 parts by weight of cationic slow-cracking emulsified asphalt per 100 parts by weight of aggregate, and an appropriate amount of water. Dry mix at 25°C for 30 seconds, add emulsified asphalt and water, wet mix for 60 seconds until the color is uniform, fill into a standard Marshall mold (φ101.6 mm), compact on both sides 75 times, demold, and cure at room temperature to obtain the mixture specimen.

[0054] Comparative Example 4 (without microcapsules)

[0055] Steps S1 to S3: No microcapsule preparation is performed.

[0056] Step S4: Based on the total mass of the aggregate, weigh 70 wt% of unaged steel slag coarse aggregate (particle size ≤15 mm, free calcium oxide content approximately 3.5 wt%), 30 wt% of limestone fine aggregate and mineral powder, 4.0 parts by weight of cationic slow-cracking emulsified asphalt per 100 parts by weight of aggregate, and an appropriate amount of water. Dry mix at 25℃ for 30 seconds, add emulsified asphalt and water and wet mix for 60 seconds until the color is uniform. Pour into a standard Marshall mold (φ101.6 mm), compact on both sides 75 times each, demold, and cure at room temperature to obtain the mixture specimen.

[0057] Comparative Example 5 (the cooling temperature was insufficient; the cooling temperature was 25°C, which is higher than the 12°C in Example 1).

[0058] Step S1: Weigh 300 parts by weight of bisphenol A type epoxy resin (E-51) and 40 parts by weight of butyl glycidyl ether and stir to mix evenly. Add 45 parts by weight of stearic acid and 10 parts by weight of hydrogenated rosin glycerol ester, heat to 85°C, and stir at 300 rpm until the mixture is completely melted and transparent. Rapidly cool to 30°C to make the mixture a supercooled liquid. Add 40 parts by weight of isopentane and stir at 200 rpm for 5 minutes to mix evenly to obtain the oil phase.

[0059] Step S2: Mix 150 parts by weight of acetic acid aqueous solution (concentration 30wt%) with 100 parts by weight of tetraethylenepentamine to obtain an aqueous phase.

[0060] Step S3: At 28℃, the aqueous phase obtained in step S2 is slowly added to the oil phase obtained in step S1 at a rate of 10 mL / min, and high-speed shear emulsification is performed at 3500 rpm for 10 minutes to form a water-in-oil primary emulsion; 50 parts by weight of hydrophobic modified nano silica (R974) is ultrasonically dispersed in 250 parts by weight of deionized water, and the external aqueous phase is obtained at 35℃; the water-in-oil primary emulsion is added to the external aqueous phase, and the shell is assembled at 2000 rpm for 15 minutes. Then the system temperature is lowered to 25℃ and maintained for 20 minutes, and the microcapsules are obtained by filtration and separation.

[0061] Step S4: Based on the total mass of the aggregate, weigh 70 wt% of unaged steel slag coarse aggregate (particle size ≤15 mm, free calcium oxide content approximately 3.5 wt%), 28.5 wt% of limestone fine aggregate and mineral powder, 1.5 parts by weight of the microcapsules prepared in Step S3 per 100 parts by weight of aggregate, 4.0 parts by weight of cationic slow-cracking emulsified asphalt per 100 parts by weight of aggregate, and an appropriate amount of water. Dry mix at 25°C for 30 seconds, add emulsified asphalt and water, wet mix for 60 seconds until the color is uniform, fill into a standard Marshall mold (φ101.6 mm), compact on both sides 75 times, demold, and cure at room temperature to obtain the mixture specimen.

[0062] Comparative Example 6 (without hydrophobically modified nano-silica, and without hydrophobic particles at the droplet interface for shell assembly)

[0063] Step S1: Weigh 300 parts by weight of bisphenol A type epoxy resin (E-51) and 40 parts by weight of butyl glycidyl ether and stir to mix evenly. Add 45 parts by weight of stearic acid and 10 parts by weight of hydrogenated rosin glycerol ester, heat to 85°C, and stir at 300 rpm until the mixture is completely melted and transparent. Rapidly cool to 30°C to make the mixture a supercooled liquid. Add 40 parts by weight of isopentane and stir at 200 rpm for 5 minutes to mix evenly to obtain the oil phase.

[0064] Step S2: Mix 150 parts by weight of acetic acid aqueous solution (concentration 30wt%) with 100 parts by weight of tetraethylenepentamine to obtain an aqueous phase.

[0065] Step S3: At 28°C, the aqueous phase obtained in step S2 is slowly added to the oil phase obtained in step S1 at a rate of 10 mL / min, and high-speed shear emulsification is performed at 3500 rpm for 10 minutes to form a water-in-oil primary emulsion; the water-in-oil primary emulsion is dispersed in 250 parts by weight of deionized water and dispersed at 2000 rpm for 15 minutes, and then the system temperature is rapidly reduced to 12°C and maintained for 20 minutes, and the product is collected by filtration.

[0066] Step S4: Based on the total mass of the aggregate, weigh 70 wt% of unaged steel slag coarse aggregate (particle size ≤15 mm, free calcium oxide content approximately 3.5 wt%), 28.5 wt% of limestone fine aggregate and mineral powder, 1.5 parts by weight of the product obtained in Step S3 per 100 parts by weight of aggregate, 4.0 parts by weight of cationic slow-cracking emulsified asphalt per 100 parts by weight of aggregate, and an appropriate amount of water. Dry mix at 25°C for 30 seconds, add emulsified asphalt and water, wet mix for 60 seconds until the color is uniform, fill into a standard Marshall mold (φ101.6 mm), compact on both sides 75 times, demold, and cure at room temperature to obtain the mixture specimen.

[0067] Comparative Example 7 (no mechanical compaction triggering, only static pressure of 1 kN applied and maintained for 5 minutes to allow the mixture to initially set)

[0068] Step S1: Weigh 300 parts by weight of bisphenol A type epoxy resin (E-51) and 40 parts by weight of butyl glycidyl ether and stir to mix evenly. Add 45 parts by weight of stearic acid and 10 parts by weight of hydrogenated rosin glycerol ester, heat to 85°C, and stir at 300 rpm until the mixture is completely melted and transparent. Rapidly cool to 30°C to make the mixture a supercooled liquid. Add 40 parts by weight of isopentane and stir at 200 rpm for 5 minutes to mix evenly to obtain the oil phase.

[0069] Step S2: Mix 150 parts by weight of acetic acid aqueous solution (concentration 30wt%) with 100 parts by weight of tetraethylenepentamine to obtain an aqueous phase.

[0070] Step S3: At 28℃, the aqueous phase obtained in step S2 is slowly added to the oil phase obtained in step S1 at a rate of 10 mL / min, and high-speed shear emulsification is performed at 3500 rpm for 10 minutes to form a water-in-oil primary emulsion; 50 parts by weight of hydrophobic modified nano silica (R974) is ultrasonically dispersed in 250 parts by weight of deionized water, and the external aqueous phase is obtained at 35℃; the water-in-oil primary emulsion is added to the external aqueous phase, and the shell is assembled at 2000 rpm for 15 minutes. Then the system temperature is suddenly dropped to 12℃ and held for 20 minutes. The microcapsules are obtained by filtration and separation.

[0071] Step S4: Based on the total mass of the aggregate, weigh 70 wt% of unaged steel slag coarse aggregate (particle size ≤15 mm, free calcium oxide content approximately 3.5 wt%), 28.5 wt% of limestone fine aggregate and mineral powder, 1.5 parts by weight of the microcapsules prepared in Step S3 per 100 parts by weight of aggregate, 4.0 parts by weight of cationic slow-cracking emulsified asphalt per 100 parts by weight of aggregate, and an appropriate amount of water. Dry mix at 25°C for 30 seconds, add emulsified asphalt and water, wet mix for 60 seconds until the color is uniform, fill into a standard Marshall mold (φ101.6 mm), apply only static pressure of 1 kN and hold for 5 minutes to preliminarily shape the mixture, demold and cure at room temperature to obtain the mixture specimen.

[0072] The following performance tests were performed on the mixture specimens obtained in Example 1 and Comparative Examples 1-7:

[0073] The void ratio was determined according to the surface-dry method in JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".

[0074] The freeze-thaw splitting strength ratio (TSR) was determined according to the freeze-thaw splitting test method in JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".

[0075] The water swelling rate was determined as follows: After curing, the initial height h0 of the Marshall specimen was measured with vernier calipers. Then, the specimen was immersed in a 60℃ constant temperature water bath for 7 days. After taking it out, the surface moisture was wiped off and the height h1 after immersion was measured. The water swelling rate was calculated according to the formula (h1−h0) / h0×100%.

[0076] The test results are shown in Table 1.

[0077] Table 1 Summary of Experimental Data

[0078] Example 1 6.7 92 0.3 Comparative Example 1 9.5 75 0.8 Comparative Example 2 9.2 78 0.7 Comparative Example 3 11.5 65 2.5 Comparative Example 4 12.8 60 3.0 Comparative Example 5 8.2 82 0.5 Comparative Example 6 8.8 79 0.7 Comparative Example 7 13.5 58 2.6

[0079] The performance test results show that the steel slag emulsified asphalt mixture specimen prepared in Example 1 is superior to Comparative Examples 1-7 in terms of porosity, freeze-thaw splitting strength ratio, and water immersion swelling rate. Analysis of Examples 1 and Comparative Examples 1-7 reveals that the gasification pressurization of the low-boiling-point power source, the sealing guidance of the phase change sealing component, the exothermic reaction between the acidic component and free calcium oxide from the steel slag, the overall synergy of the microcapsule system, the process control of the cooling treatment to form the locking layer, the support of the hydrophobic particle shell layer for the stability of the microcapsule structure, and the effect of mechanical compaction on triggering microcapsule rupture all have varying degrees of influence on the compaction effect, interfacial adhesion performance, and volume stability of the mixture specimen. This indicates that the present invention, by integrating the above components into microcapsules and synergistically triggering them during the compaction process, achieves a comprehensive improvement in the compaction performance, interfacial stability, and volume stability of unaged steel slag emulsified asphalt mixture under normal temperature conditions.

[0080] The above embodiments describe the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are only illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from the scope of the principles of the present invention, and all such changes and modifications fall within the protection scope of the present invention.

Claims

1. A method for preparing steel slag emulsified asphalt mixture, characterized in that... The specific preparation steps are as follows: Step S1: Mix epoxy resin with phase change sealing component and heat until phase change sealing component melts. After cooling, add low boiling point power source to obtain oil phase. The phase change sealing component includes fatty acid phase change material and tackifying resin. The low boiling point power source is a low boiling point organic component with a normal pressure boiling point of 20~45℃. Step S2: Mix the acidic component with the aqueous curing agent to obtain an aqueous phase, wherein the acidic component is an aqueous solution of organic acid and the aqueous curing agent is a polyamine curing agent; Step S3: The aqueous phase obtained in step S2 is added to the oil phase obtained in step S1, and emulsified to form a water-in-oil primary emulsion. The primary emulsion is then dispersed in an outer aqueous phase containing hydrophobic particles for shell assembly. After cooling, the phase change sealing component crystallizes in the gaps between the hydrophobic particles to form a locking layer and obtain microcapsules. The hydrophobic particles are hydrophobically modified nano-silica. Step S4: The microcapsules obtained in step S3 are mixed with unaged steel slag coarse aggregate, fine aggregate and / or mineral powder, emulsified asphalt and water at room temperature. After spreading, the mixture is mechanically compacted. The compaction causes the microcapsules to rupture and release acidic components. The acidic components react with the free calcium oxide in the steel slag to release heat, which promotes the melting of the phase change sealing components, the gasification of the low boiling point power source and the curing of the epoxy resin, and finally forms a steel slag emulsified asphalt mixture.

2. The method for preparing steel slag emulsified asphalt mixture according to claim 1, characterized in that: The epoxy resin mentioned in step S1 is a bisphenol A type epoxy resin; the phase change sealing component includes stearic acid and hydrogenated rosin glycerol ester; and the low-boiling-point power source is isopentane.

3. The method for preparing steel slag emulsified asphalt mixture according to claim 1, characterized in that: The acidic component in step S2 is an aqueous acetic acid solution; the aqueous curing agent is tetraethylenepentamine.

4. The method for preparing steel slag emulsified asphalt mixture according to claim 1, characterized in that: The heating temperature in step S1 is 80~90℃, and the target temperature after cooling is 25~35℃; the cooling temperature in step S3 is 10~15℃.

5. The method for preparing steel slag emulsified asphalt mixture according to claim 1, characterized in that: In step S3, the shear speed for forming the water-in-oil primary emulsion is 2000~5000 rpm; in step S4, the particle size of the unaged steel slag coarse aggregate is ≤15 mm.

6. The method for preparing steel slag emulsified asphalt mixture according to claim 1, characterized in that: Based on the total mass of the mineral aggregate, the amount of the unaged steel slag coarse aggregate is 65wt%~75wt%, and the amount of the fine aggregate and / or mineral powder is 25wt%~35wt%; per 100 parts by weight of mineral aggregate, the amount of the microcapsule is 1.0~2.0 parts, and the amount of the emulsified asphalt is 3.0~5.0 parts.

7. The application of the steel slag emulsified asphalt mixture prepared by the method according to any one of claims 1 to 6 as a road maintenance engineering material.

8. The application according to claim 7, characterized in that: The steel slag emulsified asphalt mixture is used as a road maintenance material for cold-laid thin-layer overlay construction.

Citation Information

Patent Citations

  • Waterborne epoxy resin emulsified asphalt cold-mix steel slag mixture and its preparation method

    CN114873953B

  • Modified steel slag aggregate asphalt mixture and preparation method thereof

    CN117550834B